Changes of surface dressing texture as related to time and chipping size - Yaacob, Haryati; Hainin, Mohd. Rosli; Woodward, David; Woodside, Alan (Faculty of Civil Engineering, 2008)
Surface dressing has been a popular maintenance alternative for many years. The inservice performance of surface dressing relates to balancing properties such as skid resistance against changes in time as the aggregate particles embed into the underlying road and react to trafficking. This paper summarises the development of predictive laboratory methods to better understand the inter-relationships between embedment and how performance characteristics such as skid resistance and texture depth change with time. The influence of chipping size is also discussed. The findings of this laboratory based research appear to rank materials according to their in-service performance and should result in more sustainable use of limited high quality materials for road maintenance and constructions purposes